Edukasi Self Management Menggunakan Media Audiovisual Meningkatkan Perawatan Diri dan KestabilanTekanan Darah Penderita Hipertensi - Sholihah, Nurlita Rubbi; Suryanti, Suryanti; Hartono, Hartono (Jurnal Empathy Pengabdian Kepada Masyarakat, 2023)
Background: Hypertension remains one of the most common health problems experienced by the community and can increase the risk of complications if not managed properly. The low ability of patients to self-care makes blood pressure difficult to control. This community service activity aims to improve the self-management skills of hypertensive patients through self-management education using audiovisual media. Methods: The activity was conducted in the form of counselling and self-management practice for 52 hypertensive patients in Girilayu Village, Matesih Subdistrict, Karanganyar Regency. The activity partners were the Girilayu Village community with assistance from local health workers. Education was provided door-to-door using educational videos, leaflets, and interactive discussions. Evaluation was conducted by measuring self-care abilities and blood pressure before and after the activity. Results: The results of the activity showed an increase in participants' self-care abilities from moderate to high, with an average increase of 25–30%, as well as a decrease in mean systolic and diastolic blood pressure of around 5–7% after education. This improvement illustrates an increase in participants' hard skills in managing hypertension and soft skills in the form of independence and adherence to a healthy lifestyle. Conclusion: This activity had a positive impact on improving the health status of the community and has the potential to be implemented in other areas with similar problems. It is recommended that similar activities be carried out continuously and developed into applied service programmes in the field of chronic diseases.